THE INFLUENCE OF LEADERSHIP STYLES ON THE EMPLOYEES’ MOTIVATION IN THE GOVERNMENT AGENCIES IN KEDAH, MALAYSIA - Izura Ibrahim; Nurul Husna Zaini; Nurul Amira Azmi; Hafizah Besar Sa’aid (International Journal of Accounting, Finance and Business, 2022)
Employees’ job satisfaction and performance depends on the style of leadership among their leaders. The purpose of this study is to identify the relationship between the leadership styles (transformational, transactional, and laissez-faire) and the employees’ motivation. This quantitative research was conducted through a questionnaire survey with 179 respondents that work in the government agencies in Kedah. The result shows that only transformational leadership styles significantly influence the employee motivation. The transactional leadership styles and laissez-faire leadership styles have not influenced the employee motivation in government agencies that are being studied. The findings indicate that the leadership style have direct affect with employee’s motivation. As a conclusion, the leaders in government agencies should adopt the transformational leadership style to motivate the employees. However, further research should be conducted on more government agencies in Malaysia to confirm these findings.